Color atlas of cutaneous excisions and repairs - Lee, Ken K. 1964- (Cambridge University Press, 2007)
This full-color atlas presents an in-depth pictorial display of cutaneous surgery designed for all those interested in improving their surgical skills, from students and residents to experienced surgeons across a wide range of medical specialties. It provides step-by-step instructions through a series of more than 400 detailed color photographs, including supplementary illustrations demonstrating appropriate techniques. The excisions and resulting defects featured within, although primarily centered around the head and neck, cover a variety of locations. The repairs vary in type and size in order to provide multiple options in reconstruction. The chapters are separated into anatomic regions such as the eyelid, the ear, and the scalp, allowing the reader easy access to specific anatomic defects. This atlas is the culmination of the years of experience gained by the authors in the surgical management of skin cancers.